2014
DOI: 10.3329/icpj.v3i7.19078
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of stability-indicating RP-UPLC method for simultaneous estimation of thiocolchicoside and aceclofenac in combined dosage form

Abstract: A stability indicating RP-UPLC method was developed and validated for the simultaneous determination of Thiocolchicoside (TCC) and Aceclofenac (ACF) in tablet dosage form. The chromatographic separation was carried out by Thermo Scientific UPLC Instrument, Accela 1250 Pump, auto sampler with PDA detector, using column Thermo Scientific hypersil gold C18, (50 x 2.1mm) particle size 1.9µm using 5% ammonium acetate buffer and methanol in the ratio of 40:60, pH was adjusted to 5 with ortho phosphoric acid as mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The minimum concentration levels at which ACF can be reliably detected (LOD) and quantified (LOQ) were found to be 0.0692 µg/mL and 0.2076 µg/mL respectively ( Fig. 4 and Table 3) which was more sensitive than some of the other published methods (Ravisankar et al 2013, Balan andKannappan 2014). Signal to noise (S/N) ratio for LOD and LOQ was shown in Table 3 which was also within acceptable limits.…”
Section: Resultsmentioning
confidence: 54%
“…The minimum concentration levels at which ACF can be reliably detected (LOD) and quantified (LOQ) were found to be 0.0692 µg/mL and 0.2076 µg/mL respectively ( Fig. 4 and Table 3) which was more sensitive than some of the other published methods (Ravisankar et al 2013, Balan andKannappan 2014). Signal to noise (S/N) ratio for LOD and LOQ was shown in Table 3 which was also within acceptable limits.…”
Section: Resultsmentioning
confidence: 54%
“…All the products were selectively separated and fully characterized by various 2D NMR and mass spectroscopic methods experiments. The degradation products DP-2 and DP-3 were reported as the impurities of aceclofenac [9][10][11][12][13][14]. However, to the best of our knowledge, this is the first report on the structure characterization of degradation product (DP-2).…”
Section: Resultsmentioning
confidence: 99%
“…The study showed that the degradant formed is diclofenac by comparison of its standard chromatogram in both acidic and basic stress conditions [9]. Other reports [10][11][12][13][14][15] were found on simultaneous estimation of aceclofenac along with other NSAIDs by HPLC . All the above cited literature revealed that the drug is unstable under various stress conditions tested and few other degradants were formed.…”
Section: Isolation and Structural Characterization Of Degradation Promentioning
confidence: 99%
“…The solution was filtered through a Whatman filter paper and from the filtrate, 10 mL was transferred in a 50 mL volumetric flask and the volume was made up with the mobile phase. This solution was filtered again through a 0.45 mm filter before use [5].…”
Section: Preparation Of Sample Solutionmentioning
confidence: 99%